2021
DOI: 10.1080/17476348.2021.1926988
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated hemoglobin as a predictor of mortality in severe pneumonia by COVID-19

Abstract: Objective: Determine whether the levels of glycated hemoglobin (HbA1c) measured on admission to the intensive care unit (ICU) are associated with mortality in patients with severe SARS-CoV-2 pneumonia with invasive mechanical ventilation. Design: Cohort study, retrospective, observational. A single center. Place: ICU of a second-level care hospital. Patients: Severe SARS-CoV-2 pneumonia confirmed with IMV since admission to the ICU. Interventions: none. Results: A total of 56 patients with severe pneumonia, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Similarly, a meta-analysis 28 did not find a statistically significant association between HbA1c and disease severity. Sánchez Díaz et al further explored 29 the effect of high HbA1c levels on mortality outcome in a study of 56 patients requiring invasive mechanical ventilation due to COVID-19 ARDS. They were able to show an increased mortality in univariable analysis when dichotomising patients with HbA1c ≥ 6.5%, which they could not replicate in multivariable adjusted models.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a meta-analysis 28 did not find a statistically significant association between HbA1c and disease severity. Sánchez Díaz et al further explored 29 the effect of high HbA1c levels on mortality outcome in a study of 56 patients requiring invasive mechanical ventilation due to COVID-19 ARDS. They were able to show an increased mortality in univariable analysis when dichotomising patients with HbA1c ≥ 6.5%, which they could not replicate in multivariable adjusted models.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that hyperglycemia or hemoglobin A1c (HbA1c) might be associated with a poor prognosis in critically ill patients without diabetes ( 15 ). Several studies have found that HbA1c predicts ICU mortality in COVID-19 severe pneumonia, with patients with severe COVID-19 pneumonia having a higher 28-day mortality ( 16 ). Furthermore, compared to COVID-19 patients with a diabetes diagnosis, critically ill and COVID-19 patients with HbA1c levels above 6.5% and no prior diagnosis of diabetes had the highest risk of all-cause mortality ( 17 ).…”
Section: Introductionmentioning
confidence: 99%